Blindfold game in vocabulary mastery enhancement to Indonesian EFL young learners - Permatasari, Bulan Catur; Anwar, Choiril; Nugroho, Kurniawan Yudhi; Hidayati, Nani (Universitas Islam Sultan Agung, 2024)
The objective of this study was to evaluate the effectiveness of the Blindfold game in enhancing vocabulary mastery among students. A quasi-experimental design was utilized, involving both control and experimental groups. Sixth-grade students from a Demak elementary school participated in the study, which employed a non-random sampling method. The research sample included an experimental group consisting of 22 students from class VIA and a control group of 21 students from class VIB. Data on students' vocabulary knowledge were collected through a vocabulary exam comprising 15 multiple-choice questions and 10 matching items, administered via pre-tests and post-tests. The researcher analyzed the data using a t-test and SPSS 23. The pre- and post-test scores for the experimental group were 60.91 and 78.18, respectively, while the control group achieved scores of 56.76 and 60.95. The statistical analysis indicated a significance level (2-tailed) of less than 0.05, resulting in the rejection of H0 and the acceptance of H1. In conclusion, the Blindfold game has been demonstrated to be an effective instructional tool for improving vocabulary knowledge among Indonesian EFL young learners. The game not only enhanced students' vocabulary mastery but also increased their motivation to learn English. Accordingly, it is recommended that teachers utilize diverse teaching methods to foster students' learning motivation, encouraging them to become engaged and enthusiastic participants in class.